Tobacco control policy (Jossey-Bass, 2006)
Required reading for anyone wishing to be conversant with tobacco control policy, the book is edited by Kenneth E. Warner—dean of the School of Public Health at the University of Michigan and a leading tobacco policy researcher—who leads with an overview of the field. Warner’s overview is supported by reprints of some of the field’s most significant articles, written by leading scholars and practitioners